2015
DOI: 10.1007/s10488-015-0695-0
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Help Received by Individuals with Severe Mental Disorders After a Major Healthcare Reform in Quebec: Predictors and Changes at 5-Year Follow-Up

Abstract: This study assessed predictors and changes in adequacy of help received (AHR), as perceived by 204 individuals with severe mental disorders (SMDs) transferred from a mental health institution to the community following a key healthcare reform. Adjusted perceived AHR remained stable after 2 years (T1), but decreased at 5-year follow-up (T2). Predictors of higher adjusted perceived AHR are age, severity of needs, help received from services and relatives, and number of health professionals consulted. Community m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
1
16
1
Order By: Relevance
“…The knowledge sharing variable under Interactional characteristics was associated with IPC in MH-PCTs only. This suggests the particular importance of knowledge sharing in the newly formed MH-PCTs dealing with patients mainly affected by common mental disorders and substance use disorders as well as multiple biopsychosocial needs that require sharing of information, skills, and expertise [81,82]. Consistent with our results, a number of studies demonstrated that collaboration rarely succeeds without knowledge sharing on teams [30,83].…”
Section: Discussionsupporting
confidence: 86%
“…The knowledge sharing variable under Interactional characteristics was associated with IPC in MH-PCTs only. This suggests the particular importance of knowledge sharing in the newly formed MH-PCTs dealing with patients mainly affected by common mental disorders and substance use disorders as well as multiple biopsychosocial needs that require sharing of information, skills, and expertise [81,82]. Consistent with our results, a number of studies demonstrated that collaboration rarely succeeds without knowledge sharing on teams [30,83].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, it is not surprising that 22 years of age is identified as the age at which the maximum negative impact of a disabling illness occurs . Since young people are more likely to present with multidimensional needs, health service strategies should be in place to identify and respond to a range of health and social issues with the appropriate type and intensity of intervention . We propose five key domains that make up a multidimensional outcomes framework to address the specific needs of young people presenting to health services with emerging mental illness (Box 1):…”
Section: Evidence For a Multidimensional Outcomes Frameworkmentioning
confidence: 99%
“…Of the remaining 227 papers, 190 were discounted due to either region (e.g., United States), demographic (e.g., patients with dementia), irrelevant topic (e.g., comparing treatments), unavailable full text, dissertation or book. The remaining 37 studies met inclusion criteria and were included in the final review: 19 qualitative (1735), 9 quantitative (3644), and 9 mixed methods articles (4553) (Table 1). Reoccurring themes included access to care (strategies to improve access, community level of care and families, homelessness); integration and coordination of care (scope of practice for psychiatrists/physicians, access to and coordination with psychotherapy); and gaps in care.…”
Section: Resultsmentioning
confidence: 99%